2010
DOI: 10.1080/08897071003641271
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Analysis to Assess the Effect of a Mindfulness Intervention on Self-Change for Adults in Substance Use Recovery

Abstract: Substance use is a pervasive health problem. Therapeutic community (TC) is an established substance abuse treatment but TC environments are stressful and dropout rates are high. Mindfulness-based TC (MBTC) intervention was developed to address TC stress and support self-change that could impact treatment retention. Self-change was assessed through feeling and thinking word-use in written stories of stress from 140 TC residents in a historical control group and 253 TC residents in a MBTC intervention group. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Specifically, only one study [84] demonstrated large differences between MBI and control condition in reducing negative affectivity. Conversely, the remaining 2 studies [91,97] showed no differences between treatment approaches.…”
Section: Negative Affectivitymentioning
confidence: 99%
“…Specifically, only one study [84] demonstrated large differences between MBI and control condition in reducing negative affectivity. Conversely, the remaining 2 studies [91,97] showed no differences between treatment approaches.…”
Section: Negative Affectivitymentioning
confidence: 99%
“…Recent developments in computerized text analysis have shown that counting the specific types of words that people naturally use, also called quantitative word count analysis, provides important information about their psychological health and adjustment (23,24,40). Word use has been found to differentiate between formerly, never, and currently depressed students (43) and to discriminate women with and without generalized anxiety disorder (13); it has also been found to be a marker of suicidal ideation (46), adjustment to breast cancer (40), and psychological change surrounding traumatic events (5,28,35).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness-based approaches have been successfully applied to the treatment of substance abuse and addiction (See Zgierska, et al, 2009 for Review; Bowen et al, 2009; Brewer et al, 2009; Britton et al, 2010; Liehr et al, 2010; Marcus & Zgierska, 2009; Marcus et al, 2009; Vieten, Astin, Buscemi, & Galloway 2010; Zgierska & Marcus, 2010). The efficacy of mindfulness-based approaches in substance abuse treatment is attributed to decreasing the impact of negative affect.…”
Section: Introductionmentioning
confidence: 99%